2019
DOI: 10.1002/lary.27597
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Palate and Tongue Base Surgical Treatment of Obstructive Sleep Apnea: A Systematic Review and Meta‐analysis

Abstract: Objective: To evaluate multilevel palate and tongue base surgery as a method of treatment of obstructive sleep apnea by comparing the pre-and postoperative apnea-hypopnea index.Methods: We conducted a systematic review. MEDLINE and Embase databases were searched in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for conducting systematic reviews. Two authors screened all articles and performed methodological quality assessment. Relevant articles where reviewed in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…This finding is consistent with a number of clinical studies ( Simpson et al., 2018 ). Therefore, various surgical treatments have been focused on reducing the tissue mass of this region for airway expansion ( Mulholland et al., 2019 ) and the study also found that this region was mostly affected by the type of masks ( Ebben et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a number of clinical studies ( Simpson et al., 2018 ). Therefore, various surgical treatments have been focused on reducing the tissue mass of this region for airway expansion ( Mulholland et al., 2019 ) and the study also found that this region was mostly affected by the type of masks ( Ebben et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of sleep surgery in treating OSA remains controversial 34,47 . Several surgical procedures have been proposed, including nasal surgery, 48,49 uvulopalatopharyngoplasty, 50 pharyngeal surgery, 51 tongue base surgery, 52 multilevel surgery, 53,54 maxillomandibular advancement, 55,56 hyoid surgery, 57 tracheostomy, 58 and hypoglossal nerve stimulation 59,60 . Studies have described disparities in the outcomes of different surgical procedures 61 ; accordingly, the identification of predictive factors for poor outcomes and appropriate selection of patients are critical 62,63 …”
Section: Discussionmentioning
confidence: 99%
“…It appears that there has been more discussion on soft than hard tissue surgeries in recent years. There has been a rise of bariatric surgery prior to other forms of surgeries, multilevel surgery at palate, pharynx, and tongue base, transoral robotic surgery at tongue base, and radiofrequency surgeries (66)(67)(68). The DOME technique for narrow and deep vaulted maxilla is one that was more well-known to surgeons.…”
Section: Future Developmentmentioning
confidence: 99%